Asymmetrical Modes of Outdoor Lighting Lines - V. B. Kozlovskaya; V. N. Kalechyts (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2019)
Asymmetrical modes of the outdoor lighting network can be caused by disconnecting of a part of the luminaires in order to electrical energy savings at night; also – by asymmetry of voltage in power points. The possible alternative symmetric modes of energy saving to replace the incomplete-phase operation of the line have been analyzed. Calculations of various symmetric and asymmetric modes of the lighting line were carried out without taking into account and taking into account high harmonics up to the 39th one. Calculations have been performed with the programs of MathCad software. As light sources, in the calculations the widely used luminaries with high-pressure sodium arc lamps connected through electromagnetic start-up equipment were considered. Such luminaries are sources of high harmonics, and they distort the sinusoidal voltage. The values of currents, power, power loss, voltage drop in all areas of the lighting line, the voltage at the terminals of the lamps for each phase (operating parameters) are determined. The diagrams of the voltage distribution at the points of the lighting line are plotted for the considered modes of operation. The annual electric power consumption of the lighting line has been calculated for different variants of operation, and the obtained results have been compared. When refusing to disconnection of part of the luminaires at night and using a smooth transition to a lower voltage (symmetrical) at a power point or using two-stage ballast devices, uneven illumination appears less when the level of electricity consumption is comparable. The presence of voltage asymmetry at the power point, as well as the disconnection of one phase, leads to an increase in currents, power losses and voltage. The current in the zero working conductor can exceed the currents in the phase conductors (when calculated taking into account the higher harmonics). Accounting for higher harmonics allows one to determine the operating parameters more accurately, on the basis of which the electricity power consumption can be estimated.